2009
DOI: 10.1507/endocrj.k09e-167
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Blood Rheology is Closely Associated with Arterial Stiffness in Obese Patients

Abstract: on atherosclerosis formation in obesity, it is of interest in the relationship between the rheological/microcirculatory conditions as assessed by the MC-FAN and peripheral/cetral arterial stiffness as assessed by pulsewave velocity (PWV) [8]. Our study was aimed to observe the relationship extent among obese patients. Materials and MethodsA total of 109 Japanese obese patients (body mass index (BMI) ≥ 25, 45 men and 64 women, mean age 51.3 years) were enrolled, and consisted of 88 hypertensive patients, 49 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
(16 reference statements)
0
17
1
Order By: Relevance
“…3-5 We have also reported that blood viscosity increases markedly in patients with metabolic syndrome and decreases with weight reduction. 6 However, there has been no detailed analysis using the MC-FAN of reduced blood fluidity (ie, increased blood viscosity) in smokers. In this study, the BPT was significantly correlated with the number of cigarettes smoked per day, FTND score, and Brinkman index in patients who initially visited the Smoking Cessation Clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-5 We have also reported that blood viscosity increases markedly in patients with metabolic syndrome and decreases with weight reduction. 6 However, there has been no detailed analysis using the MC-FAN of reduced blood fluidity (ie, increased blood viscosity) in smokers. In this study, the BPT was significantly correlated with the number of cigarettes smoked per day, FTND score, and Brinkman index in patients who initially visited the Smoking Cessation Clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The MC-FAN is superior to other methods in terms of accuracy and reproducibility, and evidence that it is markedly useful for the evaluation of blood fluidity and microcirculatory systems has accumulated. [4][5][6] Smoking is a major risk factor for cardiovascular diseases, associated with endothelial dysfunction, 7 but a decrease in blood fluidity in smokers or the effect of smoking cessation on viscosity has not yet been evaluated. Therefore, we measured blood fluidity in smokers, analyzed its correlation with various factors related to smoking, and examined whether quitting smoking improves fluidity.…”
mentioning
confidence: 99%
“…MC-FAN has a simple methodology and is superior to other methods regarding the accuracy of channel dimensions and high reproducibility. Furthermore, some clinical studies have reported a significant relationship between an increase in the whole blood passage time (WBPT), which is measured using MC-FAN, and cardiovascular risk factors or coronary artery disease [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is crucial to elucidate the pathophysiology of CVD development in both disorders. Hemorheologic abnormalities are considered to be a possible contributor to the CVD formation in MetS (Kotani et al, 2007;Satoh et al, 2009) and CKD (Simpson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%